Window of opportunity with PD1 blockade before chemoradiotherapy for an advanced stage clear cell carcinoma of the cervix - Marie-Gabrielle Courtès; Melpomeni Kountouri; Wenwen Wang; Jean-Christophe Tille; Patrick Petignat; Manuela Undurraga; S.Intidhar Labidi-Galy (Elsevier, 2024)
Clear cell carcinoma is a rare and very aggressive subset of cervical cancer, with poor outcome if diagnosed at advanced stage. There are few data available on the optimal management of this histotype, and treatment recommendations that include surgery and chemoradiotherapy, are essentially based on those for squamous cell carcinoma. Here we report the case of a young patient newly diagnosed with advanced stage (FIGO IIB) clear cell carcinoma of the uterine cervix who received a window of opportunity one injection of nivolumab followed by standard chemoradiotherapy. She showed a persistent complete remission after 28 months of follow-up, but developed hypothyroidism, as a consequence of immunotherapy, and required lifelong thyroid hormone replacement.